IMPLEMENTATION OF ACCOUNTING INFORMATION SYSTEM IN BLUD UPT PUSKESMAS PAHANDUT PALANGKA RAYA POST TRANSFER OF STATUS - Murdia Lestari (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2022)
Accounting information systems are so important. In services (JasPel) the workforce at BLUD UPT Puskesmas Pahandut still often occurs in calculation errors because there is no latest report on the rank of the workforce itself so that the incentives given are not in accordance with what the workforce should get based on their respective ranks or years of service. respectively. The aims of this study are to (1) describe the application of the cash disbursement cycle for labor services at the BLUD UPT Puskesmas Pahandut Palangka Raya, and to (2) describe the impact of changing the status of the BLUD UPT Puskesmas Pahandut Palangka Raya from UPTD to BLUD on the expenditure cycle. This research is a field research, with a descriptive approach. The method used in this study is a qualitative method. The subjects in this study were the Head of the TU (KASUBAG TU), the BLUD Expenditure Treasurer, financial staff other contract personnel. The data collection techniques were observation, interviews, and documentation which were then analyzed using data collection techniques, data reduction, data presentation, and drawing conclusions. The result of this research is that the BLUD UPT Puskesmas Pahandut has been able to implement an accounting information system quite well during the status transition. It's just that there are obstacles that often occur and can lead to calculation errors. The impact of the change in status led to adjustments from the puskesmas and their workforce, decreased service incentive income, and the source of funds came from BLUD revenues. Keywords: Implementation; BLUD; Transfer Status